Implementation of the quantitative Real-Time PCR for the molecular-genetic diagnostics of spinal muscular atrophy - Soloviov, O.O.; Livshits, G.B.; Podlesnaya, S.S.; Livshits, L.A. (Вiopolymers and Cell, 2010)
Aim. To develop an easy and reliable assay for quantitative analysis of the SMN1 gene exon 7 copy number with Real-Time PCR and a SYBR Green dye which can be used as a test-system for spinal muscular atrophy (SMA) diagnostics. Methods. For the quantification the SMN1 gene exon 7 copies we have used the approach, which is based on the comparison of ratio between PCR amplification of the genomic DNA sample and that of an internal standard (Albumin gene) for each subject tested. For the development and validation of the assay we tested the DNA samples from ten patients with SMA (homozygous deletion of the exon 7 in the SMN1 gene) which were previously analyzed using standard PCR-RFLP method and 42 control DNA samples from: 29 heterozygous carriers of the deletion of the exon 7 in the SMN1 gene, 13 individuals without SMN1 deletion, which were previously analyzed using linkage analysis of 2AE9.1 (D5S557) and LAS96 (D5S681) polymorphic microsatellite loci, and 10 samples from individuals of the general population. The results were calculated using standard Livak method (2–ΔΔCt method). Results. The mean ± SD of the 2–ΔΔCt ratios for the carriers of the heterozygous deletion of the exon 7 in the SMN1 gene is 0.475 ± 0.091; and for the controls – 0.909 ± 0.068. The results obtained don’t show overlapping between 2–Ct ratios at the carriers of the SMN1 heterozygous deletion and individuals without it (t =3.84, p > 0.05). Conclusions. This method can be used as a basis for creating the test-system for SMA DNA diagnostics, especially for the carrier screening. Мета роботи полягала у розробці простого і надійного методу кількісного аналізу делеції 7-го екзону гена SMN1 за допомогою ПЛР у реальному часі з барвником-інтеркалятором SYBR Green, який можна використовувати в тест-системах для діагностики спінальної м’язової атрофії (СМА). Методи. Для розробки методу визначення кількості копій гена SMN1 застосовано підхід, який базується на порівнянні параметрів ампліфікації досліджуваного зразка ДНК та зовнішнього стандарту (ген альбуміну). Для підтвердження розробленого методу проаналізовано зразки ДНК 10 паціентів із СМА (гомозиготна делеція 7-го екзону гена SMN1), 42 контрольних зразки ДНК (від 29 гетерозиготних носіїв делеції 7-го екзону гена SMN1 і 13 індивідуумів без делеціії), які вивчено методом зчеплення з поліморфними мікросателітними маркерами 2AE9.1 (D5S557) і LAS96 (D5S681), а також зразки від 10 індивідуумів з контрольної популяції. Обробку результатів проводили за допомогою стандартного методу Лівака (метод 2–ΔΔCt). Результати. Середнє значение зі стандартною похибкою показника 2–ΔΔCt для гетерозиготних носіїв делеції 7-го екзону гена SMN1 становить 0,475 ± 0,091, для нормальних контролів – 0,909 ± 0,068. Встановлено відсутність перекривання результатів аналізу для гетерозиготних носіїв делеції і нормальних контролів (t = 3,84, p > 0,05). Висновки. Розроблений метод може бути придатним для аналізу СМА у програмах молекулярно-генетичного тестування, а також як компонент тест- систем для діагностики СМА. Цель работы состояла в разработке простого и надежного метода количественного анализа делеции 7-го экзона гена SMN1 с помощью ПЦР в реальном времени с интеркалирующим красителем SYBR Green, который можно использовать в тест-системах для диагностики спинальной мышечной атрофии (СМА). Методы. Для разработки метода подсчета количества копий гена SMN1 применен подход, основанный на сравнении параметров амплификации исследуемого образца ДНК и внешнего стандарта (ген альбумина). Для подтверждения разработанного метода проанализированы образцы ДНК 10 пациентов со СМА (гомозиготная делеция 7-го экзона гена SMN1), 42 контрольных образца ДНК (от 29 гетерозиготных носителей делеции 7-го экзона гена SMN1 и 13 индивидуумов без делеции), изученных методом сцепления с полиморфными микросателлитными маркерами 2AE9.1 (D5S557) и LAS96 (D5S681), а также образцы от 10 индивидуумов из контрольной популяции. Обработку результатов проводили с помощью стандартного метода Ливака (метод 2–ΔΔCt). Результаты. Среднее значение со стандартной ошибкой показателя 2–ΔΔCt для гетерозиготных носителей делеции 7-го экзона гена SMN1 составляет 0,475 ± 0,091, для нормальных контролей – 0.909 ± 0.068. Установлено отсутствие перекрывания результатов анализа для гетерозиготных носителей делеции и здоровых индивидуумов (t = 3,84, p > 0,05). Выводы. Разработанный метод может быть использован для анализа СМА в программах молекулярно-генетической диагностики, а также как компонент тест-систем для диагностики СМА.